Death in the Early Twenty-first Century : Authority, Innovation, and Mortuary Rites - Boret, Sébastien Penmellen; Long, Susan Orpett; Kan, Sergei (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
Focusing on tradition, technology, and authority, this volume challenges classical understandings that mortuary rites are inherently conservative. The contributors examine innovative and enduring ideas and practices of death, which reflect and constitute changing patterns of social relationships, memorialisation, and the afterlife. This cross-cultural study examines the lived experiences of men and women from societies across the globe with diverse religious heritages and secular value systems. The book demonstrates that mortuary practices are not fixed forms, but rather dynamic processes negotiated by the dying, the bereaved, funeral experts, and public institutions. In addition to offering a new theoretical perspective on the anthropology of death, this work provides a rich resource for readers interested in human responses to mortality: the one certainty of human existence.
Keywords: Social sciences.; Religion and sociology.; Ethnology.; elektronické knihy; electronic books